Identifikasi Ken Dedes Dalam Arca Perwujudan Sebagai Dewi Prajnaparamita : Tinjauan Filsafat Religi dan Ikonografi - nfn. Suwardono (Berkala Arkeologi, 2007)
Among the people of Malang and its surroundings, the figure of Ken Dedes (read: Dedes) as an ancient Javanese princess who is seen as very beautiful is not new anymore. This assumption stuck on the surface in the early decades of the 19th century, when the Dutch discovered ruins in the Singosari temple complex. One of the finds from the ruins was a very beautiful statue found in the Wayang temple or E temple (according to Dutch reports), an area of the Mahayana Buddhist pantheon namely Dewi Prajnaparamita. When the area temporarily resided in the resident's residence in Malang, Monnerau, the Resident of Malang at that time connected the area of Dewi Prajnaparamita with a resident's story about Ken Dedes. From this, the initial suspicion arose that the statue of Dewi Prajnaparamita was a portrait of Ken Dedes.